EVALUATION OF IN VIVO ANTICANCER AND IMMUNOSTIMULATORY ACTIVITY OF FLOWERS OF MIMOSA PUDICA LINN. (FABACEAE) - Dasgupta, Debaprotim; Dash, Suvakanta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To investigate the in vivo anticancer and immunostimulatory activity of dichloromethane (DCM) extract of flowers of Mimosa pudica and its isolated compound 11β hydroxy-3 methoxy 1,2 dehydro crinane. Methods: The anticancer activity was performed on Ehrlich ascites carcinoma (EAC) cell line in Swiss albino mice. The activity was assessed by evaluating tumor volume, viable and nonviable tumor cell count, tumor weight, hematological, and histopathological parameters of EAC-bearing animals. The immunostimulatory activity was performed through carbon clearance, delayed type hypersensitivity (DTH), neutrophil adhesion and humoral antibody (HA) titer methods. Results: At the dose of 500 and 1000 mg/kg/day p.o for the extracts and 2.5 mg/kg/day p.o. for the isolated compound, significantly decrease the tumor volume (3.46±0.135 ml, 2.25±0.153 ml, and 1.84±0.012), increased the life span (59.32%, 76.39%, and 82.43%) and significantly (p<0.05) decreased tumor weight as compared with control. Hematological profiles were found to be nearly normal level in extract treated mice compared with tumor bearing control mice. The immunostimulatory activity was also found to be effective in the above dosage regimen. The results revealed that animals treated with above doses show a significant increase in the rate of carbon clearance from blood, increase in HA titer value, increase in neutrophil adhesion and significant (p<0.05) increase in mean paw edema in DTH reactions in dose-dependent manner. Conclusion: The results demonstrated that the extract is possessing dose-dependent anticancer activity and immunostimulatory activity attributed to the presence of crinane alkaloid.